Soil organic matter: review of research results - Georges, K; Kirkby, Roger A. (Southern Africa Development Coordination Conference (SADCC), 1988)
Research results on the use of OM to maintain soil fertility, with particular reference to bean crops in Africa, are reviewed. Aspects covered are (1) the role that soil OM plays in soil physical structure, chemical properties, and biological activities and (2) the different interactions of management practices with soil OM, namely the implications of seasonal effects on OM decomposition, nutrient cycling in cereal-legume systems, minimization of losses of OM and nutrients, sources of OM, and crop residue management. The effect of green manuring on soil physical properties and on crop performance is reviewed as well as the different sources and benefits of green manuring, mulching, and composts. Research gaps identified indicated the need for N and P cycling studies in key cropping systems of Eastern and Southern Africa, farmer verification trials on management techniques for kraal/boma manure, surveys of densely populated, land-scarce areas for local sources of OM potentially for mulching and composting and identification of complementary materials for co-composting, on- farm research on mulching effects, and evaluation of agroforestry species and systems for mulching in different agroecological conditions. (CIAT)